Mengukur Penerimaan Aplikasi Transportasi Online Menggunakan Model UTAUT 2 - Pakaya, Nikmasari; Ladiku, Rahmat (Universitas Negeri Gorontalo, 2024)
The online transportation app Maxim has become a new competitor in Indonesia's industry. This study uses the UTAUT 2 model to measure the Maxim app's acceptance in Gorontalo Province. The survey was conducted among 387 respondents, with most users being teenagers and having used the app for over a year. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Measurement model analysis showed good validity and reliability. The results of the structural model analysis revealed that effort expectancy, hedonic motivation, price value, habit, and behavioral intention significantly affected the acceptance and use of the Maxim application. While performance expectancy, social influence, and facilitating conditions are not significant. On the other hand, the experience variable as a moderator does not prove significant. These findings provide practical implications for Maxim service providers to focus on ease of use, entertainment value, competitive price offerings, and building positive habits to increase user acceptance and loyalty in Gorontalo Province.Aplikasi Maxim telah menjadi fenomena di industri transportasi online di Indonesia. Penelitian ini mengukur penerimaan aplikasi Maxim di Provinsi Gorontalo menggunakan model UTAUT 2. Survei dilakukan terhadap 387 responden, dengan mayoritas pengguna berusia remaja dan telah menggunakan aplikasi lebih dari satu tahun. Data dianalisis dengan pendekatan Partial Least Squares Structural Equation Modeling (PLS-SEM). Analisis model pengukuran menunjukkan validitas dan reliabilitas yang baik. Hasil analisis model struktural mengungkapkan bahwa effort expectancy, hedonic motivation, price value, habit, dan behavioral intention terbukti berpengaruh signifikan terhadap penerimaan dan penggunaan aplikasi Maxim. Sementara performance expectancy, social influence, dan facilitating condition tidak signifikan. Di sisi lain variabel experience sebagai variabel moderator tidak terbukti signifikan. Temuan ini memberikan implikasi praktis bagi penyedia layanan Maxim untuk berfokus pada aspek kemudahan penggunaan, nilai hiburan, penawaran harga kompetitif, dan membangun kebiasaan positif untuk meningkatkan penerimaan dan loyalitas pengguna di Provinsi Gorontalo.